Monitoring Brazilian Food Security Based on Emergy Concepts: A Proposed Approach - Rafael Araujo Nacimento; Mario Duarte Canever; Luiz Carlos Terra dos Santos; Cecília Almeida; Feni Agostinho; Biagio Fernando Giannetti (Resources)
This study enhances the discussion on food security by examining trade equity between food consumers and the supply chain from an emergy perspective. The objective is to develop a food security indicator for Brazil as a case study that provides a holistic view of the historical relationship (from 1995 to 2022) between the emergy and money received by consumers and the emergy and money supplied by the food chain. Each item in the Brazilian food basket was evaluated using the Emergy Exchange Ratio (EER) indicator, which measures the advantages and disadvantages that consumers and the food chain experience in their exchanges. The results indicate that processed food items such as oils and butter generally provide greater net emergy benefits to consumers compared to fresh food items like meat, bananas, tomatoes, and potatoes, which often favor the supply chain. Furthermore, the findings highlight that vulnerable populations face significant challenges in achieving food security due to their increased efforts to generate income relative to the emergy they receive for their social welfare. The proposed food security indicator reveals that consumers enjoyed a more balanced trade since the mid-1990s; however, this trend has recently begun to reverse, underscoring the need for policies that ensure fairer exchanges. This work contributes to discussions on food security by considering an emergy-based approach with the modified Emergy per Money Ratio (EMR) as a complement to traditionally used approaches.